PSME Code 1984 (Espana Manila, Philippines : UST Press, 1984)
The first Edition of this book entitled The Philippine Mechanical Engineering Code was initiated and completed by the code committee created by the Philippine Association of Mechanical and Electrical Engineers, (PAMEE). This new edition of the code has been revised as to the numbering system, contents and units of measurements. The PSME Metric Practice Guide is used for conversion and rounding. A description of SI (Systems International) units is included with some details of its application. Additional data are provided on weights and measurements. Matters in Metric units like refrigeration, mechanics, ISO (International Systems Organization) metric screw threads and gear calculations are added .
General -- Commercial and industrial building -- Power transmission equipment, prime movers, machines and machine parts -- Machinery danger zone and points operation -- Cranes and other hoisting equipement -- elevators, dumbwaiters, escalators and moving walks -- boilers and pressure vessels -- Heating, ventilating, refrigeration and airconditioning -- standard for indoor, outdoor general storage and fire protection systems -- Water pumping for buildings -- Piping -- Metrology -- Machine shop machinery and equipment -- manufacturing processes -- fuels and lubricants -- materials
Keywords: POWER TRANSMISSION EQUIPMENT